Wnt Signaling Inhibition Deprives Small Intestinal Stem Cells of Clonogenic Capacity - Janeckova, Lucie; Fafilek, Bohumil; Krausova, Michaela; Horazna, Monika; Vojtechova, Martina; Alberich-Jorda, Meritxell; Sloncova, Eva; Galuskova, Katerina; Sedlacek, Radislav; Anderova, Miroslava; Korinek, Vladimir (Genesis (New York, N.Y., 2016)
The Wnt pathway plays a crucial role in self-renewal and differentiation of cells in the adult gut. In the present study, we revealed the functional consequences of inhibition of canonical Wnt signaling in the intestinal epithelium. The study was based on generation of a novel transgenic mouse strain enabling inducible expression of an N-terminally truncated variant of nuclear Wnt effector T cell factor 4 (TCF4). The TCF4 variant acting as a dominant negative (dn) version of wild-type (wt) TCF4 protein decreased transcription of β-catenin-TCF4-responsive genes. Interestingly, suppression of Wnt/β-catenin signaling affected asymmetric division of intestinal stem cells (ISCs) rather than proliferation. ISCs expressing the transgene underwent several rounds of division but lost their clonogenic potential and migrated out of the crypt. Expression profiling of crypt cells revealed that besides ISC-specific markers, the dnTCF4 production downregulated expression levels of epithelial genes produced in other crypt cells including markers of Paneth cells. Additionally, in Apc conditional knockout mice, dnTCF activation efficiently suppressed growth of Apc-deficient tumors. In summary, the generated mouse strain represents a convenient tool to study cell-autonomous inhibition of β-catenin-Tcf-mediated transcription.
Keywords: Wnt pathway; Wnt Signaling Pathway; Cell Proliferation; Cre/loxP; Transcription Factor 4; Transcription, Genetic; Intestine, Small; beta Catenin; transkripční faktory BHLH-Zip; buněčná diferenciace; střevní sliznice; gene targeting; buněčné dělení; genetická transkripce; Stem Cells; transkripční faktor 4; Animals; TCF/LEF transcription factors; Cell Division; myši transgenní; gut; zvířata; Intestinal Mucosa; Mice, Transgenic; myši; tenké střevo; Basic Helix-Loop-Helix Leucine Zipper Transcription Factors; proliferace buněk; Mice; signální dráha Wnt; β-catenin; kmenové buňky; beta-katenin; Cell Differentiation